Intervenciones de enfermería en el paciente crítico con riesgo de síndrome de desuso - Chamba Zavala, Nataly Verónica (2025)
In recent decades, technological and scientific advances in the ICU have increased the survival rate of critically ill patients. However, the disuse syndrome has a mortality rate of 18.4% to 32.8%, affecting 100% of users, which is multicausal with generalized metabolic and systemic deterioration in the first 24 hours of bed rest and prolonged inactivity. The general objective of this article was to identify nursing interventions in critically ill patients at risk of disuse syndrome. It corresponds to a qualitative type of research, which was based on scientific articles published in indexed journals in the last 5 years, applied because it allowed identifying the main interventions, descriptive because the data search was performed and documentary because it was carried out by means of a bibliographic review. As a result, it was found that the main nursing interventions are: examination of level of consciousness, monitoring of vital parameters, control of delirium, agitation and pain, balanced diet, respiratory therapy, prevention of infections and skin lesions, early mobility and isometric exercises, monitoring of acid-base status, evaluation of fluid balance, application of scales: Katz, Barthel, Braden, Morse, Tinetti, MRC sum, Borg, Edmonton, RASS and the ICU-Mobility-Scale. It was concluded that nurses should periodically update their knowledge to recognize the onset of the disease and reduce the possible consequences or sequelae at the biological, psychological and social levels, making interventions that act directly in the process of maintaining or recovering the individual's health.